Rise and fire the origins, science, and evolution of the jump shot --- and how it transformed basketball forever - Fury, Shawn (New York Flatiron Books, 2016)
"It's hard to believe that there was a time when the jump shot didn't exist in basketball. When the sport was invented in 1891, players would take set shots with both feet firmly planted on the ground. Defenders controlled the sport, the pace was slower, and games would frequently end with scores fit for a football field. It took almost forty years before players began shooting jump shots of any kind and sixty-five years before it became a common sight. When the first jump shooting pioneers left the ground, they rose not only above their defenders, but also above the sport's conventions. The jump shot created a soaring offense, infectious excitement, loyal fans, and legends. Basketball would never be the same. Rise and Fire celebrates this crucial shot while tracing the history of how it revolutionized the game, shedding light on all corners of the basketball world, from NBA arenas to the playgrounds of New York City and the barns of Indiana. Award-winning journalist Shawn Fury obsesses over the jump shot, explores its fundamentals, puzzles over its complexities, marvels at its simplicity, and honors those who created some of basketball's greatest moments. Part history, part travelogue, and part memoir, Rise and Fire bounces from the dirt courts of the 1930s to today's NBA courts and state-of-the-art shooting labs, examining everything from how nets and rims affect a shooter to rivalries between shooting coaches to how the three-pointer came to rule the game. Impeccably researched and engaging, the book features interviews and profiles of legendary figures like Jerry West, Bob McAdoo, Ray Allen, and Denise Long---the first woman ever drafted by the NBA, plus dozens more, revealing the evolution of the shot over time"--Provided by publisher.
Machine generated contents note: -- SECTION ONE: IN THE BEGINNING -- Chapter One: Origins and Mysteries -- Chapter Two: Jump Shooting Marines -- Chapter Three: 1950s: Naysayers and Trendsetters -- Chapter Four: Buckets, Balls, and Shooter's Gyms -- Chapter Five: 1960s: Big Shots, Big Men -- SECTION TWO: THE JUMP SHOT TOUR -- Chapter Six: Legends, Tragedies, and Families -- Chapter Seven: Denise, Jeanette, and the Game of the Century -- Chapter Eight: The Rocket and the Splendid Splinter -- Chapter Nine: The Miracle, the Movie, and the Miss -- SECTION THREE: GUNNER'S PARADISE -- Chapter Ten: 1970s: No Conscience Required -- Chapter Eleven: The Machine -- Chapter Twelve: Bob McAdoo: The Revolutionary -- SECTION FOUR: THE MODERN GAMEChapter Thirteen: 1980s: Small Forwards, Big Scorers -- Chapter Fourteen: Bird -- Chapter Fifteen: Instructors: The Shooter, the Lab, and the Rebel -- Chapter Sixteen: 1990s and Beyond: Land of the Three -- Chapter Seventeen: The Greatest.
Keywords: Basketball -- Shooting; Basketball -- Offense; Basketball -- United States -- History